Perhitungan Harga Pokok Penjualan Pada UD. Berkah Abadi Kedungpring Lamongan - Hariyanti Hariyanti; Didik Hermawan (Universitas Sains dan Teknologi Komputer, 2020)
The determination of cost of goods sold aims to determine the price of product sales by a company. Calculation of basic price in a company to reduce the number of losses in the company. Because often the company suffered losses due to the large cost of production does not match the product selling price. The background of this study is how the calculation of cost of goods sold on manufacturing companies and how to determine the method of selling prices of products in manufacturing companies. In collecting this research data using descriptive research with quantitative qualitative data analysis techniques. Data collection method used is method of documentation and interview method. The data collected in the form of production data, sales, raw materials and others. The method used in determining cost of goods sold is using the approach of calculation method of full costing and method of variable costing.The calculation of cost of goods sold is a method of determining the price of products that charge elements of different production costs between the method of full costing with variable costing. In 2013 - 2015 UD. Eternal Blessing using Full Costing method in getting the results of 2013 amounted to Rp. 280.573.00. Year 2014 of Rp. 236.789.00. Year 2015 of Rp. 350.931,00. Meanwhile, when using Variable Costing method in getting the results in 2013 of Rp. 233701.00. Year 2014 of Rp. 209.398.00. Year 2015 of Rp. 323.299,00. Thus in knowing that between using method of full costing with variable costing happened difference. This difference is because the full costing method imposes all production costs, whereas the variable costing method does not impose fixed overhead costs. Fixed overhead costs exclude production costs. From this research it can be concluded that UD. Kedungpring Lamongan Eternal Blessings experience ups and downs of total profits per year and this study proves that cost of goods sold should pay attention to cost issues affecting the sale price.